Chronic inflammation triggered by the NLRP3 inflammasome in myeloid cells promotes growth plate dysplasia by mesenchymal cells - Chun Wang (Nature Portfolio, 2017)
Abstract Skeletal complications are common features of neonatal-onset multisystem inflammatory disease (NOMID), a disorder caused by NLRP3-activating mutations. NOMID mice in which NLRP3 is activated globally exhibit several characteristics of the human disease, including systemic inflammation and cartilage dysplasia, but the mechanisms of skeletal manifestations remain unknown. In this study, we find that activation of NLRP3 in myeloid cells, but not mesenchymal cells triggers chronic inflammation, which ultimately, causes growth plate and epiphyseal dysplasia in mice. These responses are IL-1 signaling-dependent, but independent of PARP1, which also functions downstream of NLRP3 and regulates skeletal homeostasis. Mechanistically, inflammation causes severe anemia and hypoxia in the bone environment, yet down-regulates the HIF-1α pathway in chondrocytes, thereby promoting the demise of these cells. Thus, activation of NLRP3 in hematopoietic cells initiates IL-1β-driven paracrine cascades, which promote abnormal growth plate development in NOMID mice.